DC shifts, high frequency oscillations, ripples and fast ripples in relation to the seizure onset zone. (April 2020) - Lee, Somin; Issa, Naoum P.; Rose, Sandra; Tao, James X.; Warnke, Peter C.; Towle, Vernon L.; van Drongelen, Wim; Wu, Shasha
Highlights: High frequency oscillations (HFOs) and infraslow activity (ISA) may help localize the seizure onset zone. Several studies suggest that resection of areas generating high rates of HFOs results in a favorable surgery outcome. The value of ISA in epilepsy surgery is not as well supported as that of the HFO, and additional studies are required. Pathological HFOs can be coupled to interictal spikes, associated with delta waves, or have stereotypical morphologies. Abstract: Efforts to improve epilepsy surgery outcomes have led to increased interest in the study of electroencephalographic oscillations outside the conventional EEG bands. These include fast activity above the gamma band, known as high frequency oscillations (HFOs), and infraslow activity (ISA) below the delta band, sometimes referred to as direct current (DC) or ictal baseline shifts (IBS). HFOs in particular have been extensively studied as potential biomarkers for epileptogenic tissue in light of evidence showing that resection of brain tissue containing HFOs is associated with good surgical outcomes. Not all HFOs are conclusively pathological, however, as they can be recorded in nonepileptic tissue and induced by cognitive, visual, or motor tasks. Consequently, efforts to distinguish between pathological and physiological HFOs have identified several traits specific to pathological HFOs, such as coupling with interictal spikes, association with delta waves, and stereotypical morphologies. On the opposite end of the EEG spectrum, sub-delta oscillations have been shown to co-localize with the seizure onset zones (SOZ) and appear in a narrower spatial distribution than activity in the conventional EEG frequency bands. In this report, we review studies that implicate HFOs and ISA in ictogenesis and discuss current limitations such as inter-observer variability and poor standardization of recording techniques. Furthermore, we propose that HFOs and ISA should be analyzed in addition to activity in the conventional EEG band during intracranial presurgical EEG monitoring to identify the best possible surgical margin.